The outlawed party : social democracy in Germany, 1878-1890 - Lidtke, Vernon L. (Princeton legacy library., 1966)
During the years that the German Social Democratic party organization was legally suppressed by the Socialist Law, the movement underwent a fundamental transformation in its relationship to the traditions of political democracy and socialist theory with which it began in the 1860's. This history shows how, gradually adopting Marxian economic and political theory, the Party could not abandon parliamentary participation under the Socialist Law without closing its one open legal door. Thus the Social Democrats became both ambivalent parliamentarians and ambivalent revolutionaries. Originally published in 1966. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.